Educationalisation and its implications for contemporary society - Mikiewicz, Piotr (Adult Education Discourses, 2020)
This text presents a few reflections on the processes formatting contemporary conditions for the functioning of individuals in Western society. It proposes a general presentation of the sociocultural syndrome of educationalisation. Learning (education) becomes a tool, a task, an effect (in the form of an attitude of readiness for the constant development of skills), which defines the logic of action of contemporary people. This text should be seen as a contribution to a broader analysis of social processes related to the growing importance of educational institutions in the contemporary world. The first part presents the main features of the syndrome of educationalisation as a process resulting from the expansion of formal education institutions. The author points out here the importance of school education in changing the way of peoples’ ways of thinking over the decades and in locating the value of education at the centre of Western culture. The second part of the text presents the influence of education on various spheres of functioning of individuals. The author shows how educational logic begins to regulate the activities of individuals in fields so far not associated with education.